(untitled) - Vaculík, Juraj; Bachmann, Fabian (Doprava a spoje, 2008)
Contribution is about fundamentals view in marketing and its instruments knows as marketing mix - product, price, place and promotion with spread to model of 7th P and its opportunities and risks. Marketing within the service sector will face many challenges in the future. In contribution are the opportunities and risks associated with future developments within the sector too.